2*(-2)²-(-¼)+(-2)³=
-(-2)³-(-⅕)²-5*(-⅖)+10=
(-2+2/-1)*(-2/-1-(-1)²=
(⅓*(-1)*6*(-2))²=
(0,4*(-5)*(-½)²)³=
(-2*(-¼)*8+⅕*(-2)*10)²=
(-6*⅓*(-0,5)²*⅔³*(-3)⁴)²=
√-7²-2*2³+3*(-1)⁴ ---- to wszystko pod pierwiastkiem / to kreska ułamkowa

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-24T20:25:02+01:00
2*(-2)²-(-¼)+(-2)³= 2*4 + 1/4 - 8= 8+1/4-8=1/4
-(-2)³-(-⅕)²-5*(-⅖)+10=8+ 1/25 +2+10= 20 - 1/25 = 19 24/25
(-2+2/-1)*(-2/-1-(-1)²=0 * (-2/-1-(-1) = 0
(⅓*(-1)*6*(-2))²=(-1/3 * 6 *-2)²= (-4)² = 16
(0,4*(-5)*(-½)²)³= (2/5 * -5 * 1/4)³ = (-1/2)³=-0,125
(-2*(-¼)*8+⅕*(-2)*10)²= 1/2*8-2/5*10=4-4=0
(-6*⅓*(-0,5)²*⅔³*(-3)⁴)²=-2*1/4*8/27*81=1/2 * 8/27 * 81 = 1/2 * 24 = 12
√-7²-2*2³+3*(-1)⁴ = √49 - 16 + 3 = √36=6